Genotoxic and anti-proliferative effects of aminoguanidine on gamma-irradiated MCF-7 breast cancer cells. - Danielle Cabral Fonseca; Ivette Zegarra Ocampo; Daniel Perez Vieira (Brazilian Journal of Radiation Sciences)
The intracellular production of nitric oxide is studied as a relevant phenomenon in exposure to ionizing radiation. There is evidence of local nitric oxide production in solid tumours. Its effects were observed on the relationship between their presence with tumor progression, linked to the emergence of potential genotoxic or cytotoxic damage, or loss of proliferative capacities of tumour cells. The study evaluated the effects of the administration of aminoguanidine, a selective inhibitor of an isoform of nitric oxide synthase on the frequency of genotoxic damage, loss of clonogenic potential, induction of cytotoxicity and nitrite production after exposure to ionizing radiation in radiotherapeutic doses. Human breast tumor (MCF7) cells were treated with aminoguanidine (1 or 2 mM) and irradiated by gamma radiation at doses between 0.5 and 8Gy. The study used a well stablished technique with some modifications for evaluation of genotoxic damage by frequency of micronuclei in binucleated cells. In cultures treated with 1 mM, we observed increased cytotoxicity and genotoxicity, and reduction of the clonogenic potential of the colonies. Alternatively, 2 mM aminoguanidine produced the opposite effect, apparently protecting cultures from the effects of exposures. The experiments suggested that the administration of aminoguanidine may reduce the in vitro radiossensitivity of tumors due to the increase of the frequency of genotoxic damage.